Ventilation approaches and radon control in Canadian houses - Gaskin, Janet; Zhou, Liang Grace; Li, Yunyi Ethan; Tardif, Patrique (Frontiers in Public Health, 2025)
IntroductionBalanced mechanical ventilation with heat (sensible heat only) or energy (sensible and latent heat) recovery has the potential to dilute indoor radon and may be an appropriate first step at reducing moderate indoor radon concentration in a house with mechanical exhaust only. A field study of the effectiveness of heat/energy recovery ventilation systems at reducing moderate indoor radon concentration was conducted in 13 occupied houses and three test houses in Canada. Controlled experiments were also conducted at the test houses to evaluate indoor radon concentration under different depressurization and ventilation scenarios.MethodsIn the field study of heat recovery ventilation systems (HRVs) in occupied homes, the indoor radon concentration was measured for different HRV settings within a season to estimate the effectiveness of radon reduction. In the controlled depressurization experiments in the test houses, the change in pressure of the basement relative to the subslab and of the basement, main floor and second floor relative to outdoors was evaluated for a range of mechanical exhaust ventilation scenarios.ResultsThe initial radon concentrations measured on the lower floor in the study houses with the HRV off were moderate, ranging from 91 to 312 Bq/m3, with a median of 175 Bq/m3. The median (25th–75th percentiles) effectiveness of radon reduction was 39% (29–50) for continuous HRV operation at high fan speed in the 12 field study houses where it was connected directly to the forced air furnace heating systems. In the test houses, the sustained operation of mechanical exhaust ventilation devices, however, increased the depressurization and the indoor radon concentration, and the indoor radon concentrations observed at the depressurization of −5 Pa were higher than those observed at −10 and −20 Pa.ConclusionBalanced mechanical ventilation with heat recovery was shown to be an effective radon control strategy in a field study of occupied houses with a moderate initial indoor radon concentration. Improving the energy efficiency of the existing housing stock is a priority in many countries, and including balanced mechanical ventilation systems may be an effective radon control option when conducting energy retrofits in existing houses.